Academic recovery : supporting students in academic probation - Dial, Michael T., 1986- (National Resource Center for The First-Year Experience® and Students in Transition, 2022)
"An academic resource for higher education professionals that provides guidance on how to better support students who are in endanger of or are on academic probation."-- Provided by publisher.
Keywords: Counseling in higher education.; College attendance.; Academic achievement.; College students -- Rating of.; Effectifs étudiants.; Étudiants -- Évaluation.; Academic achievement; College attendance; College students -- Rating of; Counseling in higher education